Reliable Software Technologies – Ada-Europe 2014 19th Ada-Europe International Conference on Reliable Software Technologies, Paris, France, June 23-27, 2014. Proceedings - George, Laurent.; George, Laurent.; Vardanega, Tullio.; Vardanega, Tullio. (Programming and Software Engineering, 2014)
This book constitutes the refereed proceedings of the 19th Ada-Europe International Conference on Reliable Software Technologies, Ada-Europe 2014, held in Paris, France, in June 2014. The revised 12 full papers presented together with two keynotes were carefully reviewed and selected from 68 submissions. They are organized in topical sections on formal methods; uses of ada; real-time scheduling; applications.